2016
DOI: 10.1123/ijsnem.2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Improved Time to Exhaustion But Did Not Change Alternative Maximal Accumulated Oxygen Deficit Estimated During a Single Supramaximal Running Bout

Abstract: The aim of the current study was to investigate the effects of acute caffeine supplementation on anaerobic capacity determined by the alternative maximal accumulated oxygen deficit (MAOD) in running effort. Eighteen recreational male runners [29 ± 7years; total body mass 72.1 ± 5.8 kg; height 176.0 ± 5.4cm; maximal oxygen uptake (VO) 55.8 ± 4.2 ml·kg ·min] underwent a graded exercise test. Caffeine (6 mg·kg) or a placebo were administered 1 hr before the supramaximal effort at 115% of the intensity associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 12 publications
1
30
1
1
Order By: Relevance
“…In addition, higher levels of blood lactate were observed at the end of the exercise protocol, in agreement with increased exercise workloads (Figures 1C for three-month-old mice and Figure 1E for seven-month-old mice). Even when significant, the observed ergogenic effect in both groups of animals was modest compared to the overt effect seen in humans [8,9]. Therefore, we wonder whether the mice were effectively in the blood peak of caffeine and whether it differs when the sympathetic nervous system is stimulated by physical activity [28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, higher levels of blood lactate were observed at the end of the exercise protocol, in agreement with increased exercise workloads (Figures 1C for three-month-old mice and Figure 1E for seven-month-old mice). Even when significant, the observed ergogenic effect in both groups of animals was modest compared to the overt effect seen in humans [8,9]. Therefore, we wonder whether the mice were effectively in the blood peak of caffeine and whether it differs when the sympathetic nervous system is stimulated by physical activity [28].…”
mentioning
confidence: 99%
“…The ergogenic effects of caffeine have been demonstrated in different sport modalities, namely running [8,9], cycling [10,11], rowing [12], track and field [3], team sports [4], and martial arts [13], among others.…”
mentioning
confidence: 99%
“…Posterior investigation provided additional evidence of test and retest reliability of MAOD ALT [43]. A recent study found that caffeine increased time to exhaustion at 115% of VO 2 peak, but the MAOD ALT had not increased [26]. The authors suggested that caffeine promotes improvement in exercise tolerance by its action on the central nervous system rather than by an increase in AC.…”
Section: Discussionmentioning
confidence: 99%
“…This approach assumes that the EPOC fast may correspond to the total energy used to resynthesize high-energy phosphate stores (i.e., alactic component) [24], while the O 2 equivalent from blood lactate accumulation ([La - ]) may represent the glycolytic energy cost (i.e., lactic component) [25]. A recent study has pointed out that caffeine improves supramaximal exercise endurance but not MAOD ALT , suggesting that either MAOD ALT is not sensitive enough to detect changes in AC with caffeine or that the potential effect of caffeine during supramaximal exercise is a different fatigue-related process [26]. Therefore, studies testing caffeine effects using different approaches to estimate AC are required to provide insights as to whether caffeine-induced improvement on AC can be equally detected by these different methods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no significant differences for aerobic, anaerobic lactic, anaerobic alactic and total energy expenditure were found in the present study. Regarding the anaerobic contribution in high intensity exercise, studies verifying the effect of caffeine 24 and metformin 25 showed that even with a higher time to exhaustion, there was no significant difference in the anaerobic contribution in these exercises, probably because the anaerobic energy reserve may be a finite source 26 . On the other hand, as well as CHO mouth rinse, CHO intake did not increase time to exhaustion and anaerobic contribution in physically active cycling at 110% PPO 27 .…”
Section: Discussionmentioning
confidence: 99%